Congenital tibial deficiency. Case presentation - Lazaro Martín Martínez Estupiñan; Lázaro Martínez Aparicio (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The objective of this study is to present an uncommon case. The patient is treated in the neonatology service of the University Hospital "Martyrs of April 9", during the current year, with congenital tibia deficiency. This article is written with the purpose of updating knowledge about this medical condition and providing possibilities of treatment.